Elegy for theory - Rodowick, David Norman 1952- (Harvard Univ. Press, 2014)
Rhetorically charged debates over theory have divided humanities scholars for decades. D. N. Rodowick steps back from arguments pro and con to assess why theory has become such a deeply contested concept. Far from lobbying for a return to the "high theory" of the 1980s, he calls for dialogue on an ethically inflected philosophy of the humanities